Consumer Impulse Buying Behavior for Approach in the Context to Visual Merchandising in Kathmandu (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2025)
The primary objective of this study was to examine the relation between visual merchandising dimensions and consumer impulse buying behavior in retail industry of Nepal, to understand which visual merchandising tools and techniques influences the customers most and to highlight the importance of visual merchandising concept in sales and marketing arena which helps to boost sales turnover and also create an appealing store image. The study area for this research was the retail stores of malls in Kathmandu, data were collected from respondents through questionnaire survey method. The sample population for this study was composed of shoppers who visited the malls and retail stores. This study sampled 208 customers visiting the retail stores in malls in Kathmandu city using convenience sampling technique. This study followed descriptive research design and casual comparative research design which assessed and examined the effect of visual merchandising dimensions specifically; product display, form/ mannequin display, lighting & music, shop brands name and promotional signage on consumer impulse buying behavior. Respondents’ demographic profile describing the sample population is presented in this study, followed by descriptive statistics for each of the surveys administered. The correlation analysis found that product display, form/ mannequin display, lighting & music and promotional signage had significant relationship with consumer impulse buying behavior. Similarly, regression analysis identified that product display, form/ mannequin display and promotional signage had a significant relation with consumers’ impulsivity. It is hence, concluded that consumer impulse buying is significantly impacted by product display, form/ mannequin display and promotional signage. As impulse buying has now been perceived as a common behavior, thus retailers should take the opportunity and benefit themselves from the use of different VM elements which is often termed as ‘an art of silent selling’.